Contextual factors in understanding the jumping performance of young football goalkeepers - Gonzalo Fernández-Jávega; Manuel Moya-Ramón; Iván Peña-González (Elsevier, 2024)
The aim of this study was to examine the effect of various contextual factors, such as relative age, biological maturation, or competitive level, on the jumping performance of young football goalkeepers. Vertical jump performance was evaluated in a selection of goalkeepers (n = 110) from U-14 and U-16 category teams. The sample was categorized by relative age, biological maturation, and competitive level. The results revealed a trend in the overall sample towards an overrepresentation of goalkeepers born in the early months of the year. Maturity status influenced the most in jumping performance of young goalkeepers (SJ: F = 11.27, p < .001, ηp2 = 0.187; CMJ: F = 8.72, p < .001, ηp2 = 0.162; AJ: F = 8.37, p < .001, ηp2 = 0.146), while the birth quartile had no effect on the jumping performance in the sample. Statistical differences were significant for SJ and CMJ between competitive level groups in the U-14 group only. (F = 5.37, p = .008, ηp2 = 0.186) and CMJ (F = 4.54, p = .016, ηp2 = 0.159). This study showed a greater association between maturation and jumping performance in young football goalkeepers rather than with relative age, which could influence the selection process in this field position at early ages.